Enforce tax compliance, but cautiously: The role of trust in authorities and power of authorities - Stefanos A. Tsikas (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
The "Slippery Slope Framework" hypothesizes that (an individual's) tax compliance is determined by both the tax authority's powerfulness and its trustworthiness, and that the two dimensions moderate each other. By employing a within-country fixed effects analysis for 25 European countries, this paper tests the conjecture that a slippery slope exists also on the aggregate level. Results show that both trust and power are positively correlated with higher tax compliance. Trust and power also moderate each other: the lower trust, the greater the compliance-increasing impact of power. However, the positive effect decreases with increasing coercion. Strong deterrence policies may eventually damage tax compliance.
Keywords: E62; H26; H30; 330; Tax compliance; Slippery Slope Framework; trust; power; institutions